Colchicine for preventing stroke in patients with and without intracranial atherosclerotic stenosis: a prespecified analysis of a randomized clinical trialResearch in context - Jiejie Li; Jing Jing; Xia Meng; Fu-Dong Shi; Hong-Qiu Gu; Aoming Jin; Yong Jiang; Hao Li; S. Claiborne Johnston; Graeme J. Hankey; J. Donald Easton; Xuewei Xie; et al. (EClinicalMedicine)
Summary: Background: The effect of colchicine on subsequent stroke among patients with and without symptomatic intracranial artery stenosis (sICAS) and whether age modifies such effect are not known. Methods: In this prespecified subgroup analysis of CHANCE-3, a randomized, double-blind, placebo-controlled clinical trial conducted at 244 centers in China between 11 August 2022 and 13 April 2023 (ClinicalTrials.gov number, NCT05439356), we included 7567 patients with ischemic stroke or transient ischemic attack and assessments of intracranial arteries at baseline. The primary efficacy outcome was a new stroke at 90 days. The main secondary outcome was a combined vascular event including ischemic stroke, hemorrhagic stroke, TIA, myocardial infarction, and vascular death. The primary safety outcome was any serious adverse event within 90 days. Findings: In patients with sICAS, 141 (10.5%) patients on colchicine and 115 (8.5%) on placebo had recurrent stroke within 90 days (adjusted HR 1.30, 95% CI 1.01–1.69; p = 0.04); in patients without sICAS, the corresponding event rates were 4.2% and 5.2% (adjusted HR 0.80, 95% CI 0.62–1.05; p = 0.10) (adjusted interaction p = 0.01). A significant interaction was also observed between sICAS status and the effect of colchicine on the secondary outcome of combined vascular events (adjusted p = 0.02). The interaction was more apparent in the elderly patients (adjusted p < 0.001). In the elderly patients with sICAS (n = 1648), the risk of stroke was higher in the colchicine group (n = 829, 50.3%) compared to the placebo group (n = 819, 49.7%) (adjusted HR 1.58, 95% CI 1.13–2.20; p < 0.001). There was no interaction of status of sICAS with treatment groups on primary safety outcome of any serious adverse event (p = 0.54). In patients with sICAS, 24 (1.8%) patients on colchicine and 7 (0.5%) on placebo had diarrhea within 90 days (p = 0.002). In patients without sICAS, diarrhea occurred in 43 (1.8%) patients on colchicine and in 20 (0.8%) patients on placebo (p = 0.004). Interpretation: The effect of colchicine on subsequent stroke within 90 days may differ according to the presence of sICAS. Aging might be associated with an increased risk of early recurrent stroke in the patients with sICAS receiving colchicine treatment. Future prospective studies are needed to confirm these results. Funding: National Key R&D Program of China, National Natural Science Foundation of China, the Capital's Funds for Health Improvement and Research and Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences. China Kunming Pharmaceuticals supplied colchicine and placebo. Guangdong Wesail Biotech Co. provided assistance in measurement of hsCRP levels.